Pengaruh Citra Destinasi, Perceived Value dan Experiental Marketing Terhadap Minat Berkunjung Kembali : (Studi pada Pelanggan Domestik Bali Dive Resort and SPA Tulamben) - I Komang Andre Kusuma Sardana; Gede Bayu Rahanatha (Gemawisata: Jurnal Ilmiah Pariwisata, 2024)
Nowadays, many people spend their vacation time traveling to a new destination or a destination that has already been visited. This potential must be used by a destination to increase the interest of tourists to visit again. This research was conducted at Bali Dive Resort and Spa Tulamben which is located in Tulamben village, Karangasem. The purpose of this study was to test and explain the role of destination image, perceived value, experiential marketing on revisit intention in domestic customers of Bali Dive Resort and Spa Tulamben. The sample in this study were 120 respondents. Data collection was carried out by distributing questionnaires via google form. The collected data were analysed by classical assumption test, multiple linear regression analysis and hypothesis testing. The results of this study indicate that the variables of destination image, perceived value, experiental marketing have a significant positive effect on revisit intention. The implications of this research can be taken into consideration and input for Bali Dive Resort and Spa Tulamben in maintaining the revisit intention domestic customers by considering the variables of destination image, perceived value and experiential marketing.